TINJAUAN HUKUM PELAKSANAAN DAN PENGEMBANGAN SISTEM INFORMASI DESA (SID) DI KABUPATEN SERANG - Muhamad Yusuf; Fatkhul Muin; Pipih Ludia Karsa; Diya Ul Akmal (LPPM Universitas Bina Bangsa, 2022)
The aim of this study was to figure out how the Village Information System in Serang Regency was implemented and developed. There are 326 villages in Serang Regency, all of which have access to the Village Information System. The issue is that village data is slow to update, resulting in recipients of village funds not being on target or having to double-check their information. This study used the legal empirical method with normative data analysis. The data used are primary data (Interviews and Observations) and secondary data (Legislation, Books, Journals, and relevant materials sourced from the Internet) which are then processed and narrated using words with scientific logic. According to the findings of this study, villages in Serang Regency still do not take advantage of existing information systems. The Regional Government of Serang Regency must issue regional legal regulations to define the implementation and development of the Village Information System. Furthermore, each village must prepare human resources so that the Village Information System can be implemented quantitatively and managed effectively